2020
DOI: 10.1096/fj.201901900r
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMP‐activated protein kinase during sepsis/inflammation improves survival by preserving cellular metabolic fitness

Abstract: The purpose was to determine the role of AMPK activation in the renal metabolic response to sepsis, the development of sepsis-induced acute kidney injury (AKI) and on survival. In a prospective experimental study, 167 10-to 12-week-old C57BL/6 mice underwent cecal ligation and puncture (CLP) and human proximal tubule epithelial cells (TEC; HK2) were exposed to inflammatory mix (IM), a combination of lipopolysaccharide (LPS) and high mobility group box 1 (HMGB1). Renal/TEC metabolic fitness was assessed by moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 69 publications
(86 reference statements)
3
33
1
Order By: Relevance
“…Modulation of sepsis-enhanced glycolysis with 2-DG improved the survival outcome by decreasing MKK3 phosphorylation and increasing SIRT3 expression (18). Moreover, Jin et al recently revealed that renal AMPK activation protected from sepsis-induced AKI by preserving mitochondrial function and metabolic fitness likely through SIRT3 signaling (39). The aforementioned results are consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Modulation of sepsis-enhanced glycolysis with 2-DG improved the survival outcome by decreasing MKK3 phosphorylation and increasing SIRT3 expression (18). Moreover, Jin et al recently revealed that renal AMPK activation protected from sepsis-induced AKI by preserving mitochondrial function and metabolic fitness likely through SIRT3 signaling (39). The aforementioned results are consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…AKI induced by sepsis is closely associated with excessive inflammatory responses and severe renal impairment. Indeed, the kidney is one of the earliest and most frequently affected organs during sepsis ( Bagshaw et al, 2008 ; Jin et al, 2020 ). Therefore, early intervention can prevent further exacerbation of AKI and more serious damage caused by sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that pharmacologic activation of AMPK, a master regulator of energy, promoter of OXPHOS, and inhibitor of Warburg metabolism [ 63 ], improves survival in rodents exposed to CLP. More importantly, we have demonstrated that AMPK activation decreases the development of AKI, suggesting that the survival advantage may be associated with reducing organ dysfunction [ 64 ].…”
Section: The Cellular Panic Button: Reprogramming From Oxidative Phosphorylation To Aerobic Glycolysis and Backmentioning
confidence: 99%
“…Furthermore, they demonstrated that stimulation of PGC-1α improves the survival of rodents exposed to ischemia reperfusion injury [ 69 ] and following LPS [ 51 ], suggesting that the stimulation of regulators of FAO and OXPHOS improves outcome and that a shift toward OXPHOS may follow a similar blueprint as in inflammatory cells. Activation of PGC-1α requires a coordinated sequence of phosphorylation and deacetylation by AMPK and Sirtuin 1, respectively [ 64 , 67 ]. AMPK indirectly can also activate Sirtuin 1 by increasing nicotinamide adenine dinucleotide (NAD + ) availability.…”
Section: Cellular Molecular Mechanisms To Reprogram Metabolismmentioning
confidence: 99%
See 1 more Smart Citation